Kebijakan Penjara pada Pidana Ringan dalam Hukum Pidana Yang Berkeadilan dan Berkeindonesiaan - Sahabuddin Sahabuddin; Warfian Saputra (Wajah Hukum, 2021)
There are quite a lot of problems faced by this nation in creating a just legal system regarding minor crimes (tipiring), this is because a legal system adopted by Indonesia today is a Dutch colonial heritage that is not in accordance with Indonesian cultural values, not to mention the problems The current legal system is based on the origin of written legality which is very rigid, causing the values that live in society to be increasingly eroded. For this reason, there is a need for a policy in criminal law reform in the future that is fair and Indonesian, so that the use of criminal sanctions is more appropriate and efficient in tackling crime.